2017
DOI: 10.1016/j.neurobiolaging.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

White matter damage and glymphatic dysfunction in a model of vascular dementia in rats with no prior vascular pathologies

Abstract: We investigated cognitive function, axonal/white matter (WM) changes and glymphatic function of vascular dementia (VaD) using a multiple microinfarction (MMI) model in retired breeder (RB) rats. The MMI model induces significant (p<0.05) cognitive decline that worsens with age starting at 2 weeks, which persists until at least 6 weeks after MMI. RB rats subjected to MMI exhibit significant axonal/WM damage identified by decreased myelin thickness, oligodendrocyte progenitor cell numbers, axon density, synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 49 publications
7
136
0
Order By: Relevance
“…CAA and CADASIL) characterized by protein aggregation and deposition. Glymphatic function has been assessed in several highly relevant processes to SVD including aging(28) and diseases such as microinfarction (29, 30), stroke (31), Alzheimer’s disease (AD)(32), migraine(33), and diabetes(34). Extrapolating from the current literature, we will focus on the effects that altered PVS structure and function, arterial pulsatility, and clearance have on glymphatic function.…”
Section: Glymphatic Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…CAA and CADASIL) characterized by protein aggregation and deposition. Glymphatic function has been assessed in several highly relevant processes to SVD including aging(28) and diseases such as microinfarction (29, 30), stroke (31), Alzheimer’s disease (AD)(32), migraine(33), and diabetes(34). Extrapolating from the current literature, we will focus on the effects that altered PVS structure and function, arterial pulsatility, and clearance have on glymphatic function.…”
Section: Glymphatic Systemmentioning
confidence: 99%
“…General expression of AQP4 is increased within regions of diffuse reactive glial fibrillary acidic protein (GFAP)-positive gliosis. A vascular dementia (VaD) model characterized by diffuse multiple microinfarction (MMI) was achieved by intracarotid injection of cholesterol crystals (40–70μm) in two recent studies(29, 30). Both of these studies demonstrated severe glymphatic system impairment initially, with glymphatic influx returing to baseline by 14 days after the injury.…”
Section: Glymphatic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…DM decreases neuronal dendrite outgrowth and neuronal cell survival and increases cell death of myelin‐producing oligodendrocytes 9. In the diabetic brain, ischemia induces significant white matter rarefaction, decreases axon and myelin density, and decreases the proliferation and survival of oligodendrocytes progenitor cells, and delays remyelination 53, 79, 80, 81. Loss of myelin and axon density hinders the conduction of nerve signals and interneuronal communications affecting sensorimotor functions 76.…”
Section: White Matter Damage In Diabetic Strokementioning
confidence: 99%